2008
DOI: 10.1016/j.joca.2007.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Foot progression angle and the knee adduction moment: a cross-sectional investigation in knee osteoarthritis

Abstract: A toe out FPA was associated with altered knee adduction moment waveform characteristics, extracted using PCA, in asymptomatic individuals and those with mild to moderate knee OA only. These findings are directly implicated in medial knee compartment loading. This relationship was not evident in those with severe knee OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
80
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 44 publications
(80 reference statements)
0
80
0
5
Order By: Relevance
“…So far solely gait analysis studies considered the FPA, but no studies dealing with dynamic movements such as jumps, have focused on the FPA as a central parameter inXuencing joint and motor control. During walking the FPA eVects lower extremity's joint moments (Guo et al 2007;Lynn and Costigan 2008;Rutherford et al 2008), ankle joint angles (Ho et al 2000), and muscle activation patterns (Lynn and Costigan 2008). In those studies dealing with gait analysis the FPA has primarily been observed as a parameter inXuencing knee joint moments, whereas a more exorotated foot reduces frontal knee peak joint moments, and thus minimizes knee loading compared to an internal rotated FPA (Andrews et al 1996;Guo et al 2007, Lynn andCostigan 2008;Rutherford et al 2008).…”
Section: The Fpa a Central Parameter Regulating Lateral Stretch Loadsmentioning
confidence: 99%
“…So far solely gait analysis studies considered the FPA, but no studies dealing with dynamic movements such as jumps, have focused on the FPA as a central parameter inXuencing joint and motor control. During walking the FPA eVects lower extremity's joint moments (Guo et al 2007;Lynn and Costigan 2008;Rutherford et al 2008), ankle joint angles (Ho et al 2000), and muscle activation patterns (Lynn and Costigan 2008). In those studies dealing with gait analysis the FPA has primarily been observed as a parameter inXuencing knee joint moments, whereas a more exorotated foot reduces frontal knee peak joint moments, and thus minimizes knee loading compared to an internal rotated FPA (Andrews et al 1996;Guo et al 2007, Lynn andCostigan 2008;Rutherford et al 2008).…”
Section: The Fpa a Central Parameter Regulating Lateral Stretch Loadsmentioning
confidence: 99%
“…Gait compensations can be described as the tendency of patients to compensate for localized pain and pathology by adopting probable automatic gait modifications (6). Gait patterns that alter knee joint loads or are related to pain have recently engendered particular interest, especially toe-out angle (7)(8)(9)(10)(11)(12)(13), trunk lean toward the stance leg (14 -19), and associated pelvic obliquity (15,16,20). These gait patterns are correlated with the external knee adduction moment about the knee (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…The KAdM reflects the distribution of load transferred through the medial versus the lateral compartment of the tibiofemoral joint [5,12]. In studies identifying the severity of knee OA and evaluating progression and therapy, the KAdM has often been used as an outcome measure [5,17,26,34,40,41,43].…”
mentioning
confidence: 99%